(3MGTjI aQOj Ydi GdMSjfjIs - (3GdbjUQj(B, (3GdQhej(B, (3GdMfaj, aQOj, Ydj Hf eUWai (B, (3J (B1127 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj agefG eGde fage (B...(3deG cGfJ GdQSGdI GdMSjfjI aj GdBOGH eJOGhdI Hjf GdWdGH heSJMSfI dOi Chdj GdEdHGH hefJgi LGeY dLejY eG jLJGL Edjg GdefGXQ hTQMgG ZjQ NGd Yf GdETcGd (B...s
(3BNQgG (B:s
(3hPdc Gf HYV GdGYJQGVGJ GdehQOI gfGc eGfYG ef MeO Ydi hVY GdOYhi HQCSg ceG CTGQ Edjg Hbhdg dCf eJYdbGJgG UGOQI GdeYQa GdHJI aCUHM Edi GdGSJKfGAGJ HNdGa GdGYJQGVGJ GdehQOI (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\532s
(3EjVGM Gdecfhf (B1\389s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs